Antimicrobial effect of essential oil of oregano (Origanum vulgare) against Staphylococcus aureus in chicken meat - Grande V., Lesly (2023)
The aim of this study was to evaluate the antimicrobial activity of essential oil of oregano (Origanum vulgare) against Staphylococcus aureus ATCC 25923 in chicken meat. The Minimum Inhibitory Concentration (MIC) was determined by the microdilution method in wells and the Minimum Bactericidal Concentration (MBC) to determine the survival of bacteria exposed to different concentrations of essential oil. In addition, the ability of oregano essential oil to inhibit the growth of S. aureus in chicken fillets was evaluated. A MIC of 0.5% and a CMB of 4% were obtained. Concentrations ≥1% of oregano essential oil significantly (p<0.05) reduced S. aureus counts in chicken meat at levels directly related to the applied concentration. The results showed that oregano oil has an antimicrobial effect against S. aureus ATCC 25923.